Nonlinear kalman filtering for multi-sensor navigation of unmanned aerial vehicles : application to guidance and navigation of unmanned aerial vehicles flying in a complex environment - Condomines, Jean-Philippe (Elsevier, 2018)
Nonlinear Kalman Filtering for Multi-Sensor Navigation of Unmanned Aerial Vehicles covers state estimation development approaches for Mini-UAV. The book focuses on Kalman filtering technics for UAV design, proposing a new design methodology and case study related to inertial navigation systems for drones. Both simulation and real experiment results are presented, thus showing new and promising perspectives.